2019
DOI: 10.1007/s40797-019-00115-x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Women’s Employment and Poverty Rates in OECD Countries: A Kitagawa–Blinder–Oaxaca Decomposition

Abstract: Although employment growth is propagated as being crucial to reduce poverty across EU and OECD countries, the actual impact of employment growth on poverty rates is still unclear. This study presents novel estimates of the association between macrolevel trends in women's employment and trends in poverty, across 15 OECD countries from 1971 to 2013. It does so based on over 2 million household-level observations from the LIS Database, using Kitagawa-Blinder-Oaxaca (KBO) decompositions. The results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 69 publications
0
13
0
2
Order By: Relevance
“…In terms of policy, it has long been identified in the EU and beyond that despite increases in labor force participation rates, and despite active social policy (including ECEC) to support women’s employment, poverty rates have hardly—if at all—declined (Vandenbroucke and Vleminckx 2011; Cantillon and Vandenbroucke 2014; Nieuwenhuis et al 2020). The findings presented here contribute the insight that although a rise in employment will help protect individuals and households against poverty, it also represents a displacement in who benefits from employment and who is disadvantaged by the increase in employment of others.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of policy, it has long been identified in the EU and beyond that despite increases in labor force participation rates, and despite active social policy (including ECEC) to support women’s employment, poverty rates have hardly—if at all—declined (Vandenbroucke and Vleminckx 2011; Cantillon and Vandenbroucke 2014; Nieuwenhuis et al 2020). The findings presented here contribute the insight that although a rise in employment will help protect individuals and households against poverty, it also represents a displacement in who benefits from employment and who is disadvantaged by the increase in employment of others.…”
Section: Discussionmentioning
confidence: 99%
“…Would more women work full-time jobs across OECD countries, this would further reduce inequality between households (OECD, 2015). Nieuwenhuis, Van Lancker, Collado, and Cantillon (2020) also found the rise of women's employment to be associated with a reduction in relative poverty rates.…”
Section: How Women's Earnings Affect Vertical Inequalitymentioning
confidence: 96%
“…Focusing on single mothers, Jaehrling et al (2015) found that while the introduction of the active social policy approach did increase their employment rates, it failed to reduce their poverty. In a study of the long-term trends in women's employment, Nieuwenhuis et al (2020) found that even though the households in which women are working are less likely to be at risk of poverty, the marked rise in female labour force participation that has been observed in many European (and OECD) countries in recent decades has done little to reduce poverty levels. The authors hypothesised that this is because much of the growth in women's employment has been either in households who have failed to escape poverty (in-work poverty), or in households who were not poor to begin with.…”
Section: Active Social Policymentioning
confidence: 99%